A Twelve Week Home Exercise Program to Improve the Physical Fitness in the Elderly - Tunsophon, Sakara; Deenin, Wanwisa; Janson, Benjarat (Naresuan University Journal: Science and Technology (NUJST); Vol 27 No 2 (2019): April-June 2019DO - 10.14456/nujst.2019.20, 2019)
An aging population is an increasing world phenomenon that will continue to affect Thailand, and the whole world. One of the factors for achieving a healthy body is to maintain regular physical activity. Normally, aging results experience a significant decline in physical fitness. Exercise will help to improve physical fitness, which is associated with the ability to perform daily tasks. However, suitable exercise regimes for the elderly are still a challenge. Therefore, the aim of this study was to evaluate the outcome of an easy-to-follow home exercise program for 12 weeks. The quasi experiment research design was used for this study. Thirty two healthy elderly were recruited through convenient sampling and their physical fitness assessed before the program started. They were given an exercise plan to follow at home, and were examined after 6 and 12 weeks.  All exercises were selected for safety, ease of performance, and without the use of equipment, to improve all aspects of their physical fitness. The groups were asked to perform these exercises regularly –standing on one leg, wall press ups, hamstring stretches, heel and toe raises, calf stretches, and step forward, for the allotted time 5 times a week, for 12 weeks. Comparison of the baseline and post exercise intervention measurements, demonstrated a significant improvement in agility, coordination, grip strength and balance ( P <0.01) but not in leg strength and flexibility. In conclusion, a 12 week home exercise training program is beneficial to improve the important variables of physical fitness in elderly people. An exercise frequency of five times per week is recommended in order to maintain a healthy physical function in the elderly. Keywords : home exercise program, physical fitness, elderly